Combined data assimilation of ozone tropospheric columns and stratospheric profiles in a high‐resolution CTM. (12th July 2013) - Barré, J.; Peuch, V.‐H.; Lahoz, W. A.; Attié, J.‐L.; Josse, B.; Piacentini, A.; Eremenko, M.; Dufour, G.; Nedelec, P.; von Clarmann, T.; El Amraoui, L.
Abstract Stratospheric ozone profiles from MLS and tropospheric ozone columns from IASI have been assimilated into the MOCAGE model during the month of July 2009, using a variational (3D‐FGAT) technique. This study compares the separate and combined analysis of IASI tropospheric columns and MLS stratospheric profiles, in order to investigate possible synergistic effects. The contributions on the ozone distribution of each data assimilation experiment are discussed and self‐consistency is evaluated via χ2 test, Observations minus Analyses and Observations minus Forecasts diagnostics. The results show that MLS assimilation has a significant impact on the model troposphere. An evaluation of the stratospheric distribution is made using independent MIPAS stratospheric profiles. IAGOS flights are used to evaluate the impact of the dataset assimilated in the troposphere and in the UTLS region. Comparisons to MIPAS independent observations show an improvement of the ozone vertical profile in the stratosphere and in the UTLS due to the assimilation of MLS observations. The IASI analyses show the strongest improvements on ozone distributions in the free troposphere. The combined assimilation shows the most realistic ozone fields overall in the stratosphere, UTLS and troposphere. Though neither instrument covers the entire atmospheric column alone, the combined MLS and IASI analyses show also the best agreement with the independent total ozone columns data from the OMI dataset. Bias, RMSE and correlation are significantly improved compared to the free running model. This set of validations show that the vertical structure of the ozone fields is strongly improved by assimilation. By combining the pieces of information brought by IASI and MLS in the analyses, combined assimilation provides highly realistic ozone fields.